2001
DOI: 10.1007/s004390100466
|View full text |Cite
|
Sign up to set email alerts
|

Elite swimmers and the D allele of the ACE I/D polymorphism

Abstract: A polymorphism of the human angiotensin-1-converting enzyme (ACE) gene has been identified in which the presence (insertion, I allele) of a 287-bp fragment rather than the absence (deletion, D allele) is associated with lower ACE activity. Several recent studies have shown an association of the I allele with endurance performance, it being found with excess frequency in elite distance runners, rowers and mountaineers. Other workers using heterogeneous cohorts of athletes from mixed sporting disciplines have fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
124
5
4

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(149 citation statements)
references
References 16 publications
(26 reference statements)
16
124
5
4
Order By: Relevance
“…A cohort such as that previously reported, 9 which includes swimmers and track and field athletes, without deference to event duration, is even less likely to demonstrate an ACE genotype effect, especially in light of the excess of D alleles in short distance swimmers and track and field athletes both in this study, and others. 3,8 Although the D allele has been associated with greater training-related changes in left ventricular growth 14 and VO 2 max rise 15 the mechanism underlying the association of the D allele with power oriented, anaerobic sports is most likely mediated through differences in skeletal muscle strength gain. A greater training-related increase in quadriceps muscle strength has been associated with the D allele 16 .…”
Section: Discussionmentioning
confidence: 99%
“…A cohort such as that previously reported, 9 which includes swimmers and track and field athletes, without deference to event duration, is even less likely to demonstrate an ACE genotype effect, especially in light of the excess of D alleles in short distance swimmers and track and field athletes both in this study, and others. 3,8 Although the D allele has been associated with greater training-related changes in left ventricular growth 14 and VO 2 max rise 15 the mechanism underlying the association of the D allele with power oriented, anaerobic sports is most likely mediated through differences in skeletal muscle strength gain. A greater training-related increase in quadriceps muscle strength has been associated with the D allele 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Although sprint performance is likely a polygenic trait, only a few single nucleotide polymorphisms (SNP's), namely ACTN3 R577X [1][2][3][4], ACE I/D [5][6][7] and more recently eNOS -786 T/C [8] and, IL-6 -174G/C ( ), were found to be associated with sprint performance.…”
Section: Introductionmentioning
confidence: 99%
“…Sixty-six percent of the 103 white elite swimmers who were examined in the study exhibited the presence of the D allele; this percentage was significantly higher than those in the 4 largest control populations used. 34 Tsianos and colleagues 24 drew the same conclusion by showing a significant excess of the D allele among subjects competing in swimming competitions of 1 to 10 km as opposed to those competing in races of 25 km.…”
Section: Ace and Strength Performancementioning
confidence: 88%
“…33 Studies also have shown a greater frequency of the D allele among athletes who compete in shorter-distance events. 23,24,34 Myerson and colleagues 23 found a significantly greater frequency of the D allele among Olympic sprinters running 200 m or less. These findings led Woods and colleagues 34 to investigate this relationship in elite swimmers.…”
Section: Ace and Strength Performancementioning
confidence: 98%
See 1 more Smart Citation